Kawasaki dynamics in the continuum via generating functionals evolution - Finkelshtein, D. L.; Kondratiev, Yu. G.; Oliveira, M. J. (Methods of Functional Analysis and Topology, 2012)
We construct the time evolution of Kawasaki dynamics for a spatial infinite particle system in terms of generating functionals. This is carried out by an Ovsjannikov-type result in a scale of Banach spaces, which leads to a local (in time) solution. An application of this approach to Vlasov-type scaling in terms of generating functionals is considered as well.